Electric Vehicle (EV) Markets: A Comparative Analysis Between India, Nigeria, and Indonesia - Vandana Shree; Dr. Friday Ogbu Edeh; Dr. Liem Gai Sin; Dr. Rudresh Pandey; Swarn Tiwari; Amarachi Onukele; Himanshu Kumar Gupta; Farzan K A; Ganesh Tiwari; Andra Aprillia Ayu Triana; MHD. Daffa Alzahri (AIBPM Publisher, 2024)
This study aims to provide a comparative analysis of the electric vehicle (EV) markets in India, Indonesia, and Nigeria. The analysis will encompass various aspects of the EV market, including government regulations, charging infrastructure, consumer behavior, and market penetration. The objective is to identify the primary drivers and impediments to EV adoption in these nations. The research employed a mixed-method approach, utilizing both primary and secondary data collection methods. The analysis reveals that economic factors, particularly satisfaction with EVs, significantly impact adoption, with India exhibiting higher average satisfaction than Indonesia and Nigeria. A positive correlation between satisfaction ratings in India and Indonesia suggests commonalities in consumer preferences, although data limitations hinder conclusive insights. Notably, India's policy framework emerges as more conducive to EV adoption, with a statistically significant positive impact. The study implies that economic factors, especially satisfaction, contribute significantly to India's lead in EV adoption, highlighting the crucial role of the policy framework.